Penerapan Multiplayer Pada Gim Tower Defense Menggunakan Photon Unity - Shena Star Sarwodi; Wibisono Sukmo Wardhono; Muhammad Aminul Akbar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Online multiplayer game is a game that necessarily need an internet connection and ease to be played anywhere remotely, known as an advantage of this game. Tower defense is a subgenre of strategy which purposely used to defend player's territory or property by blocking enemies as an attacker through defense structures by placing along their roadway of attack. The framework that can be used for multiplayer game development is Photon Unity. Photon Unity is a real-time multiplayer framework that has server and internet services. The objective of this study is to increase interactivity in tower defense genre games by implementing a multiplayer system using photon unity. Based on the Game Experience Questioner (GEQ) researched which used to determine the impact of implementation of this multiplayer feature, it was found that female players had more empathy and negative feelings towards their opponents. Meanwhile, male players have higher behavioral involvement. Players who have never played a real-time strategy genre have a higher sense of empathy to their opponent. Whereas, players who have played a real time strategy genre game have negative feelings and has higher behavioral involvement towards their opponents.